THE INFLUENCE OF COUNTRY OF ORIGIN, PROFITABILITY, AND LEVERAGE ON ENVIRONMENTAL DISCLOSURE (EMPIRICAL STUDY ON ENVIRONMENTALLY SENSITIVE COMPANIES) - Nadiva, Siti Haninah; Muniruddin, Said (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
In recent years the impact of industrial activities on environment has increased peoples concern. This situation gives pressure from society to management to develop environmental management and report their environmental activities. Therefore, this study aims to examine the influence of country of origin, profitability, and leverage on environmental disclosure. This study analyses the disclosure of environmental activities of four industrial sectors in Indonesia Stock Exchange (IDX) for 2017 period. The study focuses on four sectors identified as more sensitive to environment namely agriculture, basic and chemical, mining, and consumer goods industry. Forty (40) companies selected as sample, of which 10 companies represent each industry. The environmental disclosure is measured by 34 environmental indicators from GRI 4.0. Multiple linear regression analysis is utilized for the hypothesis testing within the study. The result of this study revealed that all independent variables do not simultaneously influence the dependent variable. There is no influence of country of origin, profitability, and leverage on environmental disclosure